A hybrid finite element analysis and evolutionary computation method for the design of lightweight lattice components with optimized strut diameter - Salonitis, Konstantinos; Chantzis, D.; Kappatos, Vassilios (Springer, 2016)
Components incorporating lattice structures have become very popular lately due to their lightweight nature and the flexibility that additive manufacturing offers with respect to their fabrication. However, design optimization of lattice components has been addressed so far either with empirical approaches or with the use of topology optimization methodologies. An optimization approach utilizing multi-purpose optimization algorithms has not been proposed yet. This paper presents a novel user-friendly method for the design optimization of lattice components towards weight minimization, which combines finite element analysis and evolutionary computation. The proposed method utilizes the cell homogenization technique in order to reduce the computational cost of the finite element analysis and a genetic algorithm in order to search for the most lightweight lattice configuration. A bracket consisting of both solid and lattice regions is used as a case study in order to demonstrate the validity and effectiveness of the method, with the results showing that its weight is reduced by 13.5 % when using lattice structures. A discussion about the efficiency and the implications of the proposed approach is presented.
Keywords: Lattice structures; Design optimization; Genetic algorithm; Homogenization